Identification of Damage to Plate And Disc Components On Transmission Off Highway Truck (OHT) 789C - Rabiatul Adawiyah; Herliani Herliani; M. Syahwansyah Effendi; Ahmad Hendrawan; Abdul Halim (Politeknik Negeri Samarinda, 2022)
Transmission Off Highway Truck (OHT) 789C uses the Powershift transmission type. This type of transmission uses a hydraulically activated clutch. The main advantage of this powershift transmission is its very fast response when shifting gears without having to break the connection between the engine and the transmission. One component that plays a major role in this clutch is the plate and disc, which function as a medium for conducting rotation from the engine to the transmission, and this part also functions as the main frame of the clutch to withstand the workload. So that damage often occurs in these parts. This damage can occur due to several factors. An analysis is done to get the root cause and action to fix it. The purpose of the study was to identify the damage that occurred to the plate and disc and its causes. In this study, applying the 8-step method of applied failure analysis on a plate and disc transmission 789C which experienced normal wear and tear causing transmission slip. The results of the study using the 8-step applied failure analysis method showed that the root cause of the problem with the plate and disc transmission 789C was customer negligence in maintenance so that it accelerated wear and tear on the components, which caused the plate and disc to wear up normally so that contaminated oil caused the piston selector to be jammed. Reduced oil pressure results in a lack of lubrication and a transmission slip problem occurs.